The Effect of Using Digital Concept Cartoons in Science Lesson on Students’ Achievement - Arda Danıştay Şanlıtürk; Gülçin Zeybek (Universitas Pendidikan Indonesia, 2022)
In the digital age we live in, electronic teaching materials can effectively increase students' participation in the learning and teaching process. In addition, it is known that using visual materials in science education has a positive effect on learning in this direction. The study aims to determine the effect of digital concept cartoons in the sixth-grade science course on the academic achievement of students and the retention of what is learned in the lesson and to determine the students' views on the concept cartoons applied in the lesson. This research was carried out with sequential mixed design, one of the mixed designs in which quantitative and qualitative research methods are used. The quantitative dimension of the study was conducted with a random experimental design with the pretest-posttest control group, and the qualitative dimension was carried out with a case study design to support the quantitative data and make an in-depth analysis of the data. A significant difference in favor of the experimental group was found between the post-test and retention test mean scores of the experimental and control group students participating in the study. Based on these findings, it can be said that the use of digital concept cartoons in the sixth-grade science course